The quality of groundwater in the Samawah desert (Iraq) and its impact on increasing the likelihood of severe desertification in the cultivated pasture lands. - Hussin, Athier A.; Ghazal, Kariem A. (International Journal of Psychosocial Rehabilitation, 2020)
This research examined the chemical and physical properties of the ground water in the different parts of the Samawah desert in order to assess its suitability for agricultural purposes’and whether it causes an increase in the salinization of natural pasture lands used for the purpose of agricultural production, and thus exposes them to severe desertification. Several parameters are examined for (16) wells and (3) artesian wells which are located in the different regions of Samawah desert depending on the scientfic methods of sample collection in mid - February (2019). The results showed that there are differences in the ground water aspects (chemical and physical aspects) among wells water and most of the wells water was a saline water which causes an increase in the likelihood of pasture lands being exposed to severe desertification as a result of using this water for agricultural production purposes in those lands. However, there are three wells where have a good quality of water therefore, these three wells are suitable for agricultural uses, unlike the rest of the examined wells, where the water was not suitable for agriculture or suitable for agriculture, but taking care of the soil.